Does School Leadership Matter for Student Learning in India? A Case Study of Sikkim - N. Mythili (INDIAN EDUCATIONAL REVIEW, 2017)
Leadership is a new area of focus for improving student learning in India. A study was conducted in Sikkim to understand the influence of school leadership on student learning in Indian context. Random sampling was used to select 35 schools. Rating scales were constructed and administered for school heads of secondary and senior secondary schools to self evaluate their practices. Results of correlation analysis show that school leadership practice on shared vision impacts school leadership through teacher professional development, which is directly related to school climate and child focus. These school leadership practices are influenced by leadership values, beliefs and experience of school head. They in turn mediate school processes influencing student learning indirectly through academic structures and work processes and directly through teacher professional development and child focus. It is, therefore, suggested that teacher professional development as a key leadership practice must lie with school heads for improved student learning.